2020
DOI: 10.3390/su12030852
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis: Sustainable Trends and Awarded LEED 2009 Credits in Vietnam

Abstract: Established by the U.S. Green Building Council (USGBC), the Leadership in Energy and Environmental Design (LEED) became a sustainable leader of green building rating systems in American and many other countries. In Vietnam, LEED is expected as a potential solution in improving the sustainable quality of buildings for residents and solving the housing/infrastructure demand with a limit in resource consumption and minimizing negative environmental impacts. The study analyzed the awarded LEED 2009 credits by inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…To verify this LEED criticism, it is necessary to study the empirical evidence of LEED foreign certification practices. Research in this area has recently emerged ( Pushkar, 2018a , 2018b ; Wu et al., 2018 ; Pham et al., 2020 ). Pushkar (2018a) compared LEED-NCv3 2009 Gold projects certified in two pairs of northern and southern European countries, namely, Finland versus Sweden and Turkey versus Spain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify this LEED criticism, it is necessary to study the empirical evidence of LEED foreign certification practices. Research in this area has recently emerged ( Pushkar, 2018a , 2018b ; Wu et al., 2018 ; Pham et al., 2020 ). Pushkar (2018a) compared LEED-NCv3 2009 Gold projects certified in two pairs of northern and southern European countries, namely, Finland versus Sweden and Turkey versus Spain.…”
Section: Introductionmentioning
confidence: 99%
“… Pham et al. (2020) studied LEED-NCv3 Silver, Gold, and Platinum projects certified in the southern part of Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence has accumulated regarding the long-term benefits of sustainable construction, especially improved energy efficiency, better financial returns, higher labor productivity, and ultimately, the reductions in global warming achieved [1,2]. The construction industry's huge economic contribution and high energy/resource consumption in economies around the world highlight its enormous potential for significantly reducing/mitigating climate change compared with other major sectors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified additional advantages of green buildings, such as reduced operating costs, adding 3-9% to the final value of the structure [6], and higher rental premiums of approximately 3-5% and cognitive scores [7], while those who live in them have reported sleeping an average of 46 min longer each night [8] and enjoy better indoor air quality [9]. The supporting factors that have transformed the more sustainable building industry include the green building rating systems, the most popular and well-known of which is the U.S. Green Building Council's Leadership in Energy and Environmental Design (USGBC LEED) [1,2,10]. By the end of 2019, over 146,400 projects had been registered with LEED [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation